Sub-Acute Ruminal Acidosis and non-structural carbohydrates: a study model in nutritional immunology - Luis Miguel Gómez (Revista CES Medicina Veterinaria y Zootecnia, 2014)
Nutritional immunology combines two areas of knowledge that did not interact until recently. One of the best examples studied to date is the bovine rumen. The symbiotic relationship between the host and rumen microorganisms can be altered causing a breakdown of immunological tolerance and imbalance of animal homeostasis. Dietary inclusion of supplements rich in non-structural carbohydrates is required for high yielding cows to meet their energy requirements. However, the use of those diets can lead to substantial changes in the rumen ecosystem, reducing the pH and promoting the development of subacute rumen acidosis. This generates lysis of gram-negative bacteria, release of lipopolysaccharides, breaking of immune tolerance, and activation of a cascade of inflammatory mediators with systemic effects that affect milk yield and quality. The gastrointestinal tract is the most important place where lipopolysaccharides are produced and its translocation mechanism from the rumen to peripheral circulation is still controversial. This review proposes a biological model integrating nutritional and immunological aspects of production, absorption, and mechanisms of action of lipopolysaccharides and its effects on milk production and compositional quality.